A new methodology for determining water absorption of lightweight, normal-weight and heavyweight aggregates in a viscous medium. (20th March 2018) - Fernández-Fanjul, Avelino; Tenza-Abril, Antonio José; Baeza-Brotons, Francisco
Highlights: To produce LWAC, the tendency is to saturate the LWA to minimize the absorption. A new methodology to determine the aggregates absorption in concrete is proposed. Viscous absorption is recommended for accuracy in the concrete dosage. Abstract: Water absorption in aggregates has important effects on the properties of concretes especially in lightweight aggregate concretes (LWAC). It is assumed that during the production of LWAC the lightweight aggregate (LWA) absorption is equivalent to a certain percentage of the absorption determined in an aqueous medium. A new procedure for determining the absorption by aggregates in concrete (viscous medium) is proposed. This methodology makes possible to determine the water absorption in a viscous medium and it allows specifying accurately the amount of mixing water to produce concretes.